2023
DOI: 10.1371/journal.pone.0285119
|View full text |Cite
|
Sign up to set email alerts
|

Allele mining, amplicon sequencing and computational prediction of Solanum melongena L. FT/TFL1 gene homologs uncovers putative variants associated to seed dormancy and germination

Abstract: The FT/TFL1 gene homolog family plays a crucial role in the regulation of floral induction, seed dormancy and germination in angiosperms. Despite its importance, the FT/TFL1 gene homologs in eggplant (Solanum melongena L.) have not been characterized to date. In this study, we performed a genome-wide identification of FT/TFL1 genes in eggplant using in silico genome mining. The presence of these genes was validated in four economically important eggplant cultivars (Surya, EP-47 Annamalai, Pant Samrat and Arka … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Of the 95 M2 plants, 16 were chosen to undergo screening for potential changes in their genetic makeup. Within this group, six genes belonging to the Flowering Locus T (FT)/Terminal Flower 1 (TFL1) family [26] were selected for further analysis. These genes included TFL1/Centroradialis (CEN)-like genes, namely SmTFL1, SmCEN-1, SmCEN-2 and SmCEN-4, as well as SmMFT-1 and SmMFT-2, which are members of the Mother of FT and TFL1 (MFT) gene cluster of the FT/TFL1 gene family.…”
Section: Detection Of Genotypic Variation Among the M2 Mutant Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 95 M2 plants, 16 were chosen to undergo screening for potential changes in their genetic makeup. Within this group, six genes belonging to the Flowering Locus T (FT)/Terminal Flower 1 (TFL1) family [26] were selected for further analysis. These genes included TFL1/Centroradialis (CEN)-like genes, namely SmTFL1, SmCEN-1, SmCEN-2 and SmCEN-4, as well as SmMFT-1 and SmMFT-2, which are members of the Mother of FT and TFL1 (MFT) gene cluster of the FT/TFL1 gene family.…”
Section: Detection Of Genotypic Variation Among the M2 Mutant Populationmentioning
confidence: 99%
“…We attempted to screen for mutations induced by EMS mutagenesis by targeting six selected genes belonging to the FT/TFL1 family [26]. The amplicons of the genes were derived from the control and mutant samples and were subjected to Pacio RSIItargeted amplicon sequencing.…”
Section: Genotypic Screening Of M2 Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ali et al [18] suggested that aqueous garlic (Allium sativum), SA, and methyl jasmonate (MeJA) can promote seed germination and seedling growth in eggplant. Subramaniam [19] identified some candidate genes related to dormancy traits by comparing the FT/TFL1 gene family in terms of seed dormancy using multiple genomes.…”
Section: Introductionmentioning
confidence: 99%